2006
DOI: 10.1093/jn/136.10.2558
|View full text |Cite
|
Sign up to set email alerts
|

Trans Fatty Acids in Human Milk in Canada Declined with the Introduction of Trans Fat Food Labeling

Abstract: Trans fatty acids in human milk have raised concerns because of possible adverse effects on infant growth and development. Analyses of human milk in the late 1990s in Canada showed high amounts of trans fatty acids from partially hydrogenated oils. Canada introduced labeling of trans fatty acids on retail foods in 2003. We analyzed trans and cis unsaturated and saturated fatty acids in human milk collected from 87 women in 2004-2006 and compared the levels to those in milk collected from 103 women in 1998 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
5
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 31 publications
1
61
5
2
Order By: Relevance
“…Each study used a different measure of intake. In Canada, mandatory TFA labelling combined with voluntary limits was associated with a 35% reduc- 23 and a 30% reduction in dietary intake in the general population. 26 In the United States, mandatory TFA labelling was associated with a 58% reduction in TFA levels in blood plasma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each study used a different measure of intake. In Canada, mandatory TFA labelling combined with voluntary limits was associated with a 35% reduc- 23 and a 30% reduction in dietary intake in the general population. 26 In the United States, mandatory TFA labelling was associated with a 58% reduction in TFA levels in blood plasma.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in the United States 21 found a 58% reduction in TFA in plasma following mandatory TFA labelling and two Canadian studies observed a 30% decrease in dietary intake 26 and a 35% decrease in TFA in breast milk, 23 respectively, after the introduction of a more restrictive policy. Although these studies are not directly comparable because the outcome measures were different, since the only source of TFA in plasma and breast milk is from dietary intake, the difference is worth noting.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…1 g DHA/100 g total fatty acids to 1 . 0 g DHA/100 g total fatty acids in the milk fat of women who are not taking DHA supplements (Innis & King, 1999;Friesen & Innis, 2006). This range in mean values is similar across different countries (Innis, 1992(Innis, , 2004Jensen, 1999;Yukas et al 2006).…”
Section: Maternal Dietary Lipids and Their Effect On The Composition mentioning
confidence: 85%
“…High amounts of trans-fatty acids in human milk have raised concerns because of the possible adverse effects on essential fatty acid and lipid metabolism, as well as incorporation of unusual fatty acid isomers into the infant's tissues (Innis, 2006). The levels of trans-fatty acids in human milk in Canada have now decreased with the introduction of food labelling and regulations to restrict the amounts of trans-fatty acids in retail foods (Friesen & Innis, 2006). The effects of maternal dietary fat composition on the n-6 and n-3 fatty acid composition of human milk fatty acids are clearly shown by: a consideration of the changes in human-milk fatty acids over the last 50 years; a comparison of human milk fatty acids among women following vegan or mixed diets of different fat composition; the results of controlled interventions to alter maternal dietary fat intake.…”
Section: Maternal Dietary Lipids and Their Effect On The Composition mentioning
confidence: 99%
“…Trans-fatty acid labelling of foods became mandatory in Canada in December 2005. Friesen and Innis (2006) used the relation between breast milk and dietary TFAs to predict that TFA intake of women in their study decreased from 3.4 to 2.7 to 2.2 g/day during the corresponding periods. Results from the Canadian study suggest that mandatory labelling had an immediate effect on the amount of TFAs in the food supply.…”
Section: Monitoring Compliancementioning
confidence: 99%